(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study was aimed at Specifying the level of life skills among adolescents in public and vocational high school students and its relationship to social consensus. In order to answer the study questions and verify their hypotheses, The researcher applied the life skills questionnaire and the social compatibility measure to a sample of adolescent satin public and vocational high school students in Lattakia The number of students in the sample (455) , The results of the study showed the following: . A high level of life skills among the sample members, with computational averages ranging from (4.12 problem-solving and decision-making skills hub) to (4.45 axis of communication, communication and positive interaction skills), As for the level of social compatibility, the arithmetic averages ranged from (4.60 social responsibility) to (4.69 adolescent relationship to school) and all averages were at a high level. Statistically significant differences in life skills were found depending on the gender variable, These differences were in favor of females in communication, communication and positive interaction skills, problem-solving skills and decision-making, and for males in academic skills. The research showed that there are statistically significant differences in life skills depending on the variable of the specialization in favor of professional specialization in communication and communication skills and dealing positively with others and academic skills, As for the axes of social compatibility, there were differences in the focus social responsibility, the relationship of the adolescent with his family, depending on the gender variable and these differences came in favor of the females, While there were no statistically significant differences in relation to other axes depending on the gender variable. the research showed that there were statistically significant differences in relation to the axes of social compatibility depending on the variable of the specialization in the axis of the ability to social interaction in favor of professional specialization While there were no differences in the rest of the axes, there was also a statistically significant correlation between communication and communication skills and positive interaction with others with social consensus axes (social responsibility, ability to social interaction The adolescent’s relationship with his or her family, the adolescent’s relationship with the school, the adolescent’s relationship with the local environment and the research has made a number of suggestions.